Anatomy of the perirectal fascia at the level of rectosacral fascia revisited. (9th February 2022) - Ghareeb, Waleed M; Wang, Xiaojie; Chi, Pan; Zheng, Zhifang; Zhao, Xiaozhen
Abstract: Background: The relative anatomical understanding of the perirectal fasciae is of paramount importance for the proper performance of total mesorectal excision (TME). This study was to demonstrate the planes of TME and validates the intraoperative findings using cadaveric observations. Methods: In this combined retrospective and prospective study, bilateral attachment of the rectosacral fascia (RSF) was observed in 28 cadaveric specimens (male, n = 14; female, n = 14). From January 2018 to December 2019, surgical videos of 67 patients who underwent laparoscopic TME at the Affiliated Union Hospital of Fujian Medical University (Fuzhou, China) were reviewed and interpreted with the cadaveric findings. Results: The RSF (synonym: Waldeyer's fascia) is the end of the pre-hypogastric fascia at the level of S4 and comprises two layers (upper and lower). These two layers provide double fascial protection for the venous sacral plexus. It inserts into the fascia propria of the rectum along a broad horizontal arc that merges anterolaterally in an oblique downward direction until it meets the posterolateral merge of Denonvilliers' fascia at the lateral rectal ligament (LRL). This ligament does not look like a true ligament but is more likely to be a fascial combination that cushions the rectal innervation and middle rectal vessels. Conclusions: Understanding the lateral attachment of RSF and its contribution to LRL provides invaluable surgical guidance to dissect this critical area. Therefore, lateral dissection is proposed from the anterior to the posterior direction to find the correct plane that guarantees an intact mesorectal envelope to protect the important nearby nerve structures.